Group-based measurement strategies in exposure assessment explored by bootstrapping - Hoozemans, Marco JM; Burdorf, Alex; van der Beek, Allard J.; Frings-Dresen, Monique HW; Mathiassen, Svend Erik (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'The precision of mean exposure to pushing was examined in 2 occupational groups using various combinations of the number of workers and measurements per worker. ' ' METHODS ': 'The frequency and duration of pushing of the 2 occupational groups was assessed using onsite observation. All data were divided into successive periods of 30 minutes of observation. The precision of the group mean exposure to pushing was expressed by 90% confidence intervals obtained by bootstrapping. The effect on the confidence interval of varying numbers of workers and numbers of periods per worker was examined. ' ' RESULTS ': 'For both occupational groups there was little precision to be gained when >10 workers were observed. Within the maximum number of workers used in the bootstrap simulations, it appeared that, beyond 10 workers, the confidence intervals decreased by <5% for every worker that was added, when each worker was observed at least 8 periods of 30 minutes. If workers were observed exactly 4 periods of 30 minutes per worker, an additional 4 workers were required to compensate for the loss of precision. An unbalanced strategy with approximately 8 periods of 30 minutes per worker hardly decreased the precision of the group mean, however. ' ' CONCLUSIONS ': 'The precision of the group-based mean exposure to pushing is influenced by the number of workers observed and by the number of repeated measurements per worker. In the planning of measurement strategies, it is advisable to account for possible sources of variance in advance and to assess the exposure variability.
Keywords: accuracy; bootstrapping; epidemiology; exposure assessment; group-based measurement strategy; manual materials handling; observation; occupation; precision